3D reconstruction of skin pathological tissue: the understanding of microrelief pattern and dermal ridge. Issue 2 (28th August 2013) - Oh, Ga Na; Yoon, Jung Hee; Kye, Hee Sang; Kim, Dai Hyun; Kim, Jong Yeob; Choi, Jae Eun; Seo, Soo Hong; Kye, Young Chul; Ahn, Hyo Hyun; Rhyu, Im Joo
<x xml:space="preserve">Abstract</x> Aim Most studies about the structures of the human skin have been on the general histologic features of the skin. The purpose of this study was to understand the relationship between the microrelief (MR) pattern and histologic structure of the human skin, and to find the usefulness of the three‐dimensional reconstruction (3DR) technique of pathological skin tissue. Materials, Subjects, and Methods Human skin specimens were obtained from the medial forearm, abdomen, and volar aspects of the finger tips of cadavers. Two‐dimensional surface‐viewed images of the skin showing MR patterns were obtained using dry dermoscopy. Histologic structures of the skin were evaluated by 3D images obtained using the 3DR technique. Results MR was deeper and wider in the abdomen than in the medial side of the forearm. In the medial side of the forearm, 10.27 rete ridges were distributed in a plateau, on average. In the abdomen, about 14.37 rete ridges were distributed in a plateau. From 3DR technique, MR pattern thought to be a superordinate concept to rete ridges. Conclusion The 3DR technique was useful and may allow a better understanding of the pathogenetic changes in the skin surface in aging skin.